Instagram as A Media to Enhance Writing Skill of Students in Langsa - Nonnie Nurmala Sari; Nina Afrida (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2020)
This research is carried out to investigate how the uses of Instagram application to improve students’ writing skill. The participant of this research is three students of seventh semester from English Department of IAIN Langsa in academic Years 2020/2021 who have been selected through purposive sampling based on certain characteristics. In here, there are 3 students. This research used qualitative method to gain the data; observation and documentation. Based on the results, they used Instagram features; photo and video sharing and social network to share their mind and daily activity on it. Therefore, they can use it to find many accounts that they wanted. And then, the researcher found that the participants searched and followed several educational accounts that contain learning English content. Concequently, the participants’ writing ability improve after they convey their ideas on Instagram. As the result, they were able to practice and apply what they have learnt before in writing English caption actively on their Instagram accounts. It also can be proven from their writing score which participant 1 obtained 83 score, participant 2 obtained 87 score and participant 3 obtained 62 score in writing English in the manner of using proper grammar, spelling, punctuation, appropriate content, appropriate vocabulary, and conveying clear information.